Effects of cytoplasmic inheritance on preweaning traits of Hereford cattle - Mezzadra Carlos Alberto; Melucci Lilia Magdalena; Corva Pablo Marcelo; López Valiente Sebastián; Rípoli María Verónica; Lirón Pedro; Giovambattista Guillermo (Genetics and Molecular Biology, 2005)
The influence of cytoplasmic inheritance on birth and weaning weight was evaluated in an experimental Hereford herd. Data on 1,720 records for birth and weaning weights from calves born between 1963 and 2002 were studied. Variance components were estimated using MTDFREML procedures and an animal model was fitted for each trait. Direct and maternal additive effects and permanent environment and maternal lineage effects were treated as random, while year and month of birth, age of dam and sex of the calf were treated as fixed. Identification of maternal lineages was based on pedigree information. The contribution to phenotypic variance of cytoplasmic lineages defined by pedigree information was negligible for both traits. Mitochondrial genotypes of cows present in the herd in 2002 were analyzed by single strand conformation polymorphism (SSCP) analysis. Only five different genotypes were identified among 23 maternal lineages. All the animals with records were assigned to maternal genotypes based on pedigree information. The statistical analysis was repeated, removing maternal lineage from the model and including mitochondrial genotype as a fixed effect. No evidence of genotype effects was detected. These results suggest a negligible effect of the mitochondrial genome on the preweaning traits of this Hereford herd.